Strategic impact of mobility on organizations - Golovkova, Anna (Science and Transport Progress, 2014)
Purpose. The current rapid social and economic developments show mobility as the most important factor of economic growth, social and cultural progress. Mobile technology has undergone a sea change over the past ten years. The evolution of mobility is about creating better ways to change the world. It will increasingly shape our lives and thinking in ways we cannot fully anticipate. Mobile revolution is a global reality which creates new opportunities and challenges for all companies in the world. Methodology. Proposed methodological approach is based on a comprehensive assessment of the strategic impact of mobility on the organization as a major tool to improve competitiveness and efficiency of the company. During the research have been used both qualitative and quantitative methods. As a result, the article provides bridges between the field of mobility, organization science, information systems, and certain aspects of philosophy. Findings. This research provides a glimpse into the fast-evolving world of mobile technology and maybe even faster evolving world of organizations. The research is designed to understand the strategic impact of mobility on organizations, and evaluate the benefits of integration of these new technologies into the company. The research comprised of an extensive literature review, observation of existing practices, and semi-structured interviews geared toward understanding the strategic impact of mobility on organization and its employees. Originality. The research findings suggest three main strategic implications of mobility: (1) improve working process; (2) increase internal communication and knowledge sharing; and (3) enhance sales and marketing effectiveness. Practical value. The use of mobile technology and it impact on organizational change and strategy, stability and development of competitive advantage allow the company to ensure the effectiveness of its business. Mobility can dramatically transform the company by finding their feet in almost every sector and it has a profound impact on both customers as well as employees. Mobility solutions are growing across business portfolios of company and driving by the need to increase productivity. They improve decision making, with increased near real-time access through mobile channels that help to improve internal employee interaction, customer collaboration, network building and information sharing.